2009
DOI: 10.3928/01477447-20090301-05
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Intramedullary Nailing of Femoral Diaphyseal Fractures Caused by Low-velocity Gunshots

Abstract: The purpose of this study was to evaluate the results of retrograde intramedullary nailing of femoral diaphyseal fractures caused by low-velocity gunshots. Seventy-three patients (68 men and 5 women) with 74 femoral diaphyseal fractures caused by gunshots were treated with reamed, retrograde, statically locked intramedullary nailing. The main outcome measures were fracture union, the need for additional operations, shortening, angular deformity, postoperative knee range of motion, and complication rate. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…2 We found that 18% of the patients in our group had associated injuries. These include a whole array of additional soft tissue and extremity injuries secondary to the gunshot wounds to significant life-threatening injuries, including abdominal and pelvic injuries.…”
Section: Nowotarski and Brumbackmentioning
confidence: 82%
See 1 more Smart Citation
“…2 We found that 18% of the patients in our group had associated injuries. These include a whole array of additional soft tissue and extremity injuries secondary to the gunshot wounds to significant life-threatening injuries, including abdominal and pelvic injuries.…”
Section: Nowotarski and Brumbackmentioning
confidence: 82%
“…Femur fractures are the most common orthopaedic injury due to gunshots 2 and locked intramedullary nailing is the mainstay of treatment for diaphyseal femur fractures. 3 Femur fractures from ballistic injuries, in particular, are often comminuted which may complicate pre-operative planning and affect outcomes (Figures 1a and 1b).…”
Section: Introductionmentioning
confidence: 99%
“…To be able to use this device with gunshot femur fractures may be an advantage in certain cases. We are aware of only two clinical case series of retrograde IM nailing for gunshot femur fractures [2,9] but none comparing retrograde and antegrade nailing for patients with gunshot femur fractures. To our knowledge, our study is the first to compare the two groups with regard to the end points of knee sepsis and other complications, anesthetic and operative times, blood loss, and fracture union.…”
Section: Discussionmentioning
confidence: 99%
“…Cannada et al [2] retrospectively reviewed 73 patients with 74 gunshot femur fractures treated with reamed retrograde nailing at two institutions. Thirty-five patients (48%) were followed an average of 7 months after surgery, with no reported knee sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation